2011
DOI: 10.1371/journal.pone.0016042
|View full text |Cite
|
Sign up to set email alerts
|

It Takes Two to Tango: Defining an Essential Second Active Site in Pyridoxal 5′-Phosphate Synthase

Abstract: The prevalent de novo biosynthetic pathway of vitamin B6 involves only two enzymes (Pdx1 and Pdx2) that form an ornate multisubunit complex functioning as a glutamine amidotransferase. The synthase subunit, Pdx1, utilizes ribose 5-phosphate and glyceraldehyde 3-phosphate, as well as ammonia derived from the glutaminase activity of Pdx2 to directly form the cofactor vitamer, pyridoxal 5′-phosphate. Given the fact that a single enzyme performs the majority of the chemistry behind this reaction, a complicated mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 45 publications
5
35
1
Order By: Relevance
“…Moreover, the network of intrasubunit and intersubunit interactions zippering the C-terminal region in place would appear to be poised to coordinate cross-talk between two neighboring subunits. We have previously demonstrated that PDX1 displays high cooperativity in relation to the binding of the R5P substrate for which the C terminus is essential (12,14). Therefore, this structure of PDX1.3 serves to capture the fundamental essence of the C terminus in linking neighboring catalytically poised subunits.…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the network of intrasubunit and intersubunit interactions zippering the C-terminal region in place would appear to be poised to coordinate cross-talk between two neighboring subunits. We have previously demonstrated that PDX1 displays high cooperativity in relation to the binding of the R5P substrate for which the C terminus is essential (12,14). Therefore, this structure of PDX1.3 serves to capture the fundamental essence of the C terminus in linking neighboring catalytically poised subunits.…”
Section: Significancementioning
confidence: 99%
“…Loss of phosphate and water from R5P as well as the incorporation of ammonia (from glutamine in the presence of PDX2) result in a chromophoric intermediate likely to be unique to PLP synthase, which has been observed spectroscopically (8)(9)(10) but has eluded precise structural characterization. The reaction can only proceed further in the presence of G3P, which is assumed to take place in the P2 site and is where the final product PLP has been observed in X-ray crystal structures (10,12,18). A pertinent question is how the intermediate is transferred from the P1 to the P2 site.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Although PLP is essential for all living beings, only plants and microorganisms are able to synthesize it de novo. Two mutually exclusive biosynthetic routes are known [3]: (a) the deoxyxylulose 5-phosphate (DXP)-dependent pathway, present in Escherichia coli and in a restricted number of other eubacteria [4], which is a multistep process involving seven enzymes, and (b) the so-called DXP-independent pathway, which is present in plants and most bacteria and relies on the action of the PLP synthase complex, formed by subunits encoded by pdxS and pdxT genes [5][6][7]. Many bacteria (e.g.…”
Section: Introductionmentioning
confidence: 99%